La legalidad de los fondos de remediación ambiental: el caso de la OEFA en la experiencia peruana* - Martin Tirado, Richard J. (Revista de Derecho, 2019)
This paper analyzes environment protection in the Peruvian order. It focuses on thesituation of the application of sanctions in environmental matters by the OEFA.It analyzes the correct exercise of this power within the framework of the principlesof administrative sanctioning law. In order to do this, it makes an appropriate balancebetween economic development and protection of the environment. In addition, westudy the enforcement regime of sanctions and their relationship with environmentalremediation funds.
Keywords: Sanctions; environment; OEFA